2020
DOI: 10.1038/s41436-020-0926-y
|View full text |Cite
|
Sign up to set email alerts
|

Alaska Native genomic research: perspectives from Alaska Native leaders, federal staff, and biomedical researchers

Abstract: Meaningful engagement of Alaska Native (AN) tribes and tribal health organizations is essential in the conduct of socially responsible and ethical research. As genomics becomes increasingly important to advancements in medicine, there is a risk that populations not meaningfully included in genomic research will not benefit from the outcomes of that research. AN people have historically been underrepresented in biomedical research; AN underrepresentation in genomics research is compounded by mistrust based on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
(42 reference statements)
0
18
0
1
Order By: Relevance
“…The long-standing history of worldwide systematized oppression, discrimination, and colonization has created a contemporary world in which individuals of non-European ancestry often also identify with communities that have been exposed to oppression and exclusion. In the research realm, including the field of human genetics and genomics, instances of oppression and exclusion such as research abuses and eugenic sterilization have led to mistrust among populations that have been, [19][20][21][22] and continue to be, marginalized and underrepresented in research. 23,24 Underrepresentation is problematic from both a scientific and an ethical point of view.…”
Section: The Representation Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The long-standing history of worldwide systematized oppression, discrimination, and colonization has created a contemporary world in which individuals of non-European ancestry often also identify with communities that have been exposed to oppression and exclusion. In the research realm, including the field of human genetics and genomics, instances of oppression and exclusion such as research abuses and eugenic sterilization have led to mistrust among populations that have been, [19][20][21][22] and continue to be, marginalized and underrepresented in research. 23,24 Underrepresentation is problematic from both a scientific and an ethical point of view.…”
Section: The Representation Problemmentioning
confidence: 99%
“…However, there is no one right way to conduct community engagement, and not all methodologies are transferable to every research project, population, and set up. 20,[50][51][52][53][54][55][56] Nevertheless, certain aspects of community engagement are important to consider throughout the research cycle. Table 1 highlights the collaborative nature of research with the community of interest and outlines some of the steps that will facilitate respectful engagement and ultimately more successful research efforts.…”
Section: Guidance For Researchersmentioning
confidence: 99%
“…The concerns mentioned by Navajo respondents were similar to those voiced by other American Indian ( Chadwick et al, 2019 ) and Alaska Native ( Hiratsuka et al, 2020a ; Hiratsuka et al, 2020b ) communities, namely that considerations for effective and socially responsible research partnerships should be taken into consideration. Past unethical practices which affected tribal communities ( Bowekaty and Davis, 2003 ; Mello and Wolf, 2010 ) continue to drive many of the concerns that the Navajo community voiced.…”
Section: Discussionmentioning
confidence: 83%
“…Native nations are increasingly using tribal codes to set standards and expectations, exerting their jurisdiction over data, interests, places, and issues both on and off reservations ( National Congress of American Indians, 2019a ; Hiraldo et al, 2020 ). Here we share some of the ways that tribes address some of the more complex issues of tribal research oversight, including jurisdiction off tribal lands and protection of individual and collective interests, to spur Native nations to create and strengthen codes as guides to use of the CARE Principles with their peoples, lands, knowledges, and resources.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…The NIH Genomic Data Sharing policy requires federally-funded investigators to deposit de-identified data into federal databases to promote secondary analyses ( National Institutes of Health, 2014 ). However, the policy allows a data sharing exception that recognizes some tribal laws may not permit broad data sharing ( Hiratsuka et al, 2020 ). Some tribal laws and policies dictate that all data generated from a research study is property of the tribe and all data must be returned to the tribe at the conclusion of the study.…”
Section: Introductionmentioning
confidence: 99%